The ribosome inhibitor chloramphenicol induces motility deficits in human spermatozoa: A proteomic approach identifies potentially involved proteins - Bisconti, Marie; Leroy, Baptiste; Gallagher, Meurig T.; Senet, Coralie; Martinet, Baptiste; Arcolia, Vanessa; Wattiez, Ruddy; Kirkman-Brown, Jackson C.; Simon, Jean-François; Hennebert, Elise (Frontiers in Cell and Developmental Biology, 2022)
Mature spermatozoa are almost completely devoid of cytoplasm; as such it has long been believed that they do not contain ribosomes and are therefore not capable of synthesising proteins. However, since the 1950s, various studies have shown translational activity within spermatozoa, particularly during their in vitro capacitation. But the type of ribosomes involved (cytoplasmic or mitochondrial) is still debated. Here, we investigate the presence and activity of the two types of ribosomes in mature human spermatozoa. By targeting ribosomal RNAs and proteins, we show that both types of ribosomes are localized in the midpiece as well as in the neck and the base of the head of the spermatozoa. We assessed the impact of cycloheximide (CHX) and chloramphenicol (CP), inhibitors of cytoplasmic and mitochondrial ribosomes, respectively, on different sperm parameters. Neither CHX, nor CP impacted sperm vitality, mitochondrial activity (measured through the ATP content), or capacitation (measured through the content in phosphotyrosines). However, increasing CP concentrations induced a decrease in total and progressive motilities as well as on some kinematic parameters while no effect was observed with CHX. A quantitative proteomic analysis was performed by mass spectrometry in SWATH mode to compare the proteomes of spermatozoa capacitated in the absence or presence of the two ribosome inhibitors. Among the ~ 700 proteins identified in the different tested conditions, 3, 3 and 25 proteins presented a modified abundance in the presence of 1 and 2 mg/ml of CHX, and 1 mg/ml of CP, respectively. The observed abundance variations of some CP-down regulated proteins were validated using Multiple-Reaction Monitoring (MRM). Taken together, our results are in favor of an activity of mitochondrial ribosomes. Their inhibition by CP results in a decrease in the abundance of several proteins, at least FUNDC2 and QRICH2, and consequently induces sperm motility def